(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The kinetics of the effect of ethanol on iron content of ashed cow liver was investigated. The work revealed that the cow liver contained a very high quantity of iron. The effect of alcohol distilled from palm wine was tested kinetically on the measured concentration of the iron in the ashed cow liver. The depletion in the concentration of the iron was monitored spectrophotometrically at specific time intervals. The analysis showed a gradual decrease in the concentration of iron in the ashed cow liver extract. The initial iron content in the ashed cow liver was 22.6130 mg/l. After 10 minutes of reaction of the local ethanol with the cow liver extract, the quantity of the iron reduced to 7.5443 mg/l. at the end of 90 minutes, the concentration of iron further reduced to 5.3624 mg/l. the half life, rate of reaction, rate constant and order of the reaction were determined. The pH of the reaction mixture was almost constant throughout the time interval of measurement. The average pH was measured to be 6.52, being weakly acidic. The results showed that ethanol reduced or destroyed the concentration of iron present in a biological system.